(untitled) (Journal of Pharmaceutical Negative Results, 2023)
This research was conducted with the aim of comparing women's perception of positive feedback related to appearance from their husbands, based on body image levels in married women in Tehran. The statistical population of this research was made up of married women with normal BMI in Tehran in 1400-1401. 233 people were investigated using a simple random sampling method by implementing a virtual questionnaire. The tools used in the research included Littleton's body image questionnaire (2005) and the perception questionnaire of positive feedback related to appearance including five scenarios that were presented in the form of an internet questionnaire. In this research, the difference in women's scores between five types of feedback and the total score of all feedbacks and body image was investigated using the covariance analysis method and with the statistical control of the age variable. The findings showed that the total score of feedbacks and the feedback score of denying the existence of defects in the high and low body image groups were different, and no difference was observed in the scores of other feedbacks in the high and low body image groups. According to the results of this research, it can be said that positive body image is one of the factors that cause positive perception of some types of positive feedback related to appearance in women.